Trends in Area Production and Productivity of Sesame: Analysis of Bundelkhand Region of Uttar Pradesh - Tripathi, Shyam Mani; Kalia, Abhishek; Mishra, Bhanu Prakash; Mishra, Snehal; Mishra, Dheeraj; Shukla, Gaurav (Indian Journal of Extension Education, 2023)
Sesame seeds are often referred to as seeds of immortality.  Due to the root system, the crop does well under drought stress, making the Bundelkhand region more suitable for growing sesame than other districts in Uttar Pradesh. The coefficient of Variation and the Cuddy-Della-Valle Index were computed to determine the degree of instability. The relative importance of acreage and yield to the expansion of sesame production was determined by calculating the area effect, yield effect, and interaction effect. Results showed that in Jalaun, both the sesame area and production increased at a compound annual growth rate of 0.17 percent and 0.20 percent, respectively, while in other districts of Bundelkhand, they remained relatively stable or declined. On the other hand, it was found that productivity was falling across the seven districts of the region. According to the CDVI values, Chitrakoot had the highest variability in area (125.45) while Jalaun had the highest variability in production (181.7) as well as productivity (53.45). In the whole Bundelkhand, the strongest interaction effect between area and yield growth was found.